VR-embedded BIM immersive system for QS engineering education - Wang, Chen; Li, Heng; Kho, Song Yuan (John Wiley & Sons, 2018)
Information communications technology (ICT) has been implemented in the construction sector but there is not yet any immersive system to integrate virtual reality (VR) and building information modeling (BIM) for quantity surveying (QS) practice and education. Aiming to develop a VR-embedded BIM immersive system for quantity surveying practice and education, experiments using Autodesk Revit 2016, Autodesk 3ds Max Design 2015, and Unity were conducted in this study. The developed VR-embedded BIM immersive system for quantity surveying practice and education consists of two main components, namely: Immersive System (Head-mounted display/360-degree display) and Non-immersive systems (Desktop VR). The virtual reality application could help improving QS practitioners' and QS students' understanding on the architectural design using VR walkthrough to navigate the virtual 3D building model, thus to improve the efficiency of decision making and the precision in quantity surveying work.